Outcomes with bridging radiation therapy prior to chimeric antigen receptor T-cell therapy in patients with aggressive large B-cell lymphomas - Manzar, Gohar S.; Pinnix, Chelsea C.; Dudzinski, Stephanie O.; Marqueen, Kathryn E.; Cha, Elaine E.; Nasr, Lewis F.; Yoder, Alison K.; Rooney, Michael K.; Strati, Paolo; Ahmed, Sairah; Nze, Chijioke; Nair, Ranjit; et al. (Frontiers in Immunology, 2025)
BackgroundSelect patients with relapsed/refractory aggressive B cell lymphoma may benefit from bridging radiation (bRT) prior to anti-CD19-directed chimeric antigen receptor T cell therapy (CAR-T). Here, we examined patient and treatment factors associated with outcomes and patterns of failure after bRT and CAR-T.MethodsWe retrospectively reviewed adults with diffuse large B-cell lymphoma (DLBCL) who received bRT prior to axicabtagene ciloleucel, tisagenlecleucel, or lisocabtagene maraleucel between 11/2017-4/2023. Clinical/treatment characteristics, response, and toxicity were extracted. Survival was modeled using Kaplan-Meier or Cox regression models for events distributed over time, or binary logistic regression for disease response. Fisher’s Exact Test or Mann-Whitney U methods were used.ResultsOf 51 patients, 25.5% had bulky disease and 64.7% had Stage III/IV disease at the time of RT. Comprehensive bRT alone to all disease sites was delivered to 51% of patients, and 29.4% were additionally bridged with systemic therapy. Median follow-up was 10.3 months (95% CI: 7.7-16.4). Overall response rate (ORR) was 82.4% at 30 days post-CAR-T infusion. Median overall survival (OS) was 22.1 months (6.6-not reached) and the median progression-free survival (PFS) was 7.4 months (5.5-30). OS/PFS were 80% (66-99)/78% (64-87) at 1-year, and 59% (44-71)/54% (40-67) at 2-years, respectively. Comprehensive RT to all sites of disease correlated with improved PFS and OS, p ≤ 0.04. Additionally, ECOG ≥2 and Stage III/IV disease predicted poor OS (p ≤ 0.02). Disease bulk, IPI ≥3, and non-GCB histology were poor predictors for disease-specific survival (DSS), p<0.05. The latter two, as well as bRT dose of ≤30 Gy predicted worse PFS (p<0.05). Among patients with advanced stage disease, comprehensive bRT to all sites of disease (n=10) was not associated with improved OS and PFS compared to focal bRT (n=23), p>0.17. No difference was seen in bridging RT vs. chemoRT. Twenty-six patients developed relapse (50.9%), of which 46% was in-field. Risk of in-field relapse correlated with bulky disease (OR=7, 95% CI: 1.2-41, p=0.03) and lack of response at 30 day post-CAR-T evaluation (OR=16.8, 95% CI: 1.6-176, p=0.02), but not with bRT dose (p=0.27).ConclusionbRT and CART is a good treatment strategy for select patients with aggressive B cell lymphoma. Comprehensive bRT including all sites of disease is associated with improved outcomes.